Unity and differentiation of legal regulation for the implementation of the right to work in certain categories of employees - Ye. Yu. Podorozhnii (Bulletin of Kharkiv National University of Internal Affairs, 2023)
It has been proven that labour relations are a legal relationship between an employer and an employee, which is established on a voluntary basis with regard to the use by the former (i.e., the employer) of the latter’s (i.e., the employee’s) ability to work and is expressed in mutual rights and obligations. It has been noted that in order for legal regulation to be fair, effective and appropriate, it should be based on a number of principles which determine the key priorities and vectors of legal regulation. To a large extent, the principles ensure the unity and integrity of the legal system and the legal regulation mechanism.An emphasis is placed on the fact that certain categories of employees are employees for whom the current legislation, due to their physiological and social (including professional) properties (characteristics, signs, traits), provides for additional guarantees and/or benefits, some other advantages in working conditions compared to ordinary employees, and in some cases, increased requirements for their responsibility.It has been generalised that the application of the principle of unity and differentiation in the legal regulation of the implementation of the right to work in certain categories of employees is a prerequisite for unimpeded access and inclusion of persons with certain specific physiological and/or social traits considered to be legally significant into the common legal space within which relations on the use of hired labour arise, develop, change and terminate.It has been noted that the unity of legal regulation ensures a non-discriminatory approach to providing different individuals with the opportunity to realise their abilities and capacity to work through the conclusion of an employment contract. In turn, the differentiation of legal regulation allows taking into account the specific features of these employees and providing them with fair working conditions and adequate protection in accordance with their capabilities and needs due to these features.